DEFINING FEATURES WEAR CRANKSHAFT MODERN DIESEL (Municipal economy of cities. Series: «Economy science», 2013)
The features assess wear crankshafts modern diesel using the method which involves the use of a dial indicator (neck meter). The results of the study wears crankshafts diesels D49, which took place in locomotive repair depot Osnova, Poltava and Poltava diesel locomotive factory, and the results obtained EDTB Poltava. Proposed recommendations for the use of the results.